Individual and social variables and their effect on Case/Care Manager Job Satisfaction: an exploratory study - Cosentino, Chiara; Bettuzzi, Morena; Campioli, Giulia; Di Marco, Valeria; Giacopuzzi, Giulia; Marinoni, Ivana; Orlandini, Lorenzo; Palermo, Angelo; Pattacini, Siria; Artioli, Giovanna (Acta Biomedica Atenei Parmensis, 2017)
Background and aims: The Case/Care Manager (CCM) is a new position for in the Italian National Health Service scenario. Job satisfaction plays a key role for the CCM to engage in his work, accomplishing it in a complete. Nurses’ job satisfaction is a complex construct and many different variables can influence it: personal characteristics, cultural characteristic, social characteristic, organizational characteristic, and environmental characteristic. The main aim of this study is to assess the job satisfaction in a sample of CCM and to assess if and how Social Variables (organizational climate and health) and Individual (socio-demographic variables, coping strategies, emotion regulation) relate to the CCM job satisfaction. Methods: This study has a quantitative exploratory cross-sectional design. Participants were Nurse CCM with or without specific training who filled a battery of questionnaires : Job Satisfaction Survey (JSS) , section three of ICONAS questionnaire, section five of the Multidimensional Organizational Health Questionnaire (MOHQ), anamnestic sheet, Coping Orientation to the Problems Experienced (COPE-NVI-25), and Emotion Regulation Questionnaire (ERQ). The battery was administered online on the website of Italian Case Manager, Italian Association of Care Manager, and IPASVI Colleges. It was also distributed during the National Congress for Case Manager in Padua. Results: 103 participants took part in the study. The total mean score of JSS was 117,28 (S.D.=21,12). The emotional regulation strategy most used was the “Cognitive Response”, and the most used Coping strategy was “Problem Oriented”. There were significant correlations between JSS and Social variables in the total score (ICONAS r=.574 p